Entrepreneurship development in the Balkans : perspective from diverse contexts - Ramadani, Veland; Kjosev, Sasho; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2023)
Entrepreneurship Development in the Balkans directly engages questions of innovation and risk management within various types of entrepreneurship, including female, social, migrant, and corporate entrepreneurship in the context of the Balkans: Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Kosovo, Montenegro, North Macedonia, Romania, Serbia, Slovenia and Türkiye. This collection of in-depth studies represents a comprehensive state-of-the-art picture of entrepreneurship and small business management issues. It provides primary theoretical and empirical evidence that offers a brighter view of these fields from the perspective of the Balkans and includes contributions of highly reputed authors and experts from the region and beyond. Entrepreneurship Development in the Balkans appeals to regional and international researchers interested in learning more about entrepreneurship and small business management in the Balkans. Lab for Entrepreneurship and Development is Emerald's innovative book series on the study of entrepreneurship and development, striving to set the agenda for advancing research on entrepreneurship in the context of finance, economic development, innovation, and the society at large.
Foreword / Leo-Paul Dana -- Chapter 1. Entrepreneurship development in the balkans: Past, present, and future / Veland Ramadani, Sasho Kjosev, and Bruno S. Sergi -- Chapter 2. Family ties shaping the entrepreneurial intentions / Ivona Mileva, Nadezda Pop-Kostova, and Nadica Jovanovska Boshkovska -- Chapter 3. How is social entrepreneurship pursuing the path of development? Regional perspectives in the western balkans / Stefan Chichevaliev, Stojan Debarliev, and Aleksandra Janeska Iliev -- Chapter 4. Green entrepreneurship and firm performance: The case of albania / Gadaf Rexhepi, Hyrije Abazi Alili, Selajdin Abduli, Sadudin Ibraimi, and Rasim Zuferi -- Chapter 5. Entrepreneurship ecosystem in bosnia and herzegovina: Perspectives and challenges / Ramo Palalic, Ognjen Ridic, Tomislav Jukic, Abdul Wahab Aidoo, Goran Ridic, and Mohammad Rezaur Razzak -- Chapter 6. Entrepreneurial implementation intentions among Bulgarian stem students: Facilitators and constraints / Desislava I. Yordanova, Albena Pergelova, Fernando Angulo-Ruiz, and Tatiana S. Manolova -- Chapter 7. Social entrepreneurship: Perspective of croatia / Marko Kolakovic, Mladen Turuk, and Ivan Turcic -- Chapter 8. Digital entrepreneurship and disruptive innovation in the greek maritime industry: The case of harbor lab / Daphne Halkias, Mark Esposito, Tatiana Harkiolakis, Jordi Diaz, and Nicholas Mmaduabuchi Ikpogu -- Chapter 9. Informal entrepreneurship in kosovo: An institutionalist approach / Isa Mustafa, Justina Pula-Shiroka, Besnik A. Krasniqi, Veland Ramadani, and Liridon Kryeziu -- Chapter 10. Multi-context analysis of the environment for the development of entrepreneurship in montenegro / Boban Melovic and Dragana Cirovic -- Chapter 11. Sustainable entrepreneurship in north macedonia: Challenges and perspectives / Marsela Thanasi-Boçe, Selma Kurtishi-Kastrati, Veland Ramadani, and Rasim Zuferi -- Chapter 12. Gender differences in early-stage entrepreneurship: The case of Romanian entrepre
Includes bibliographical references and index.
Print version record.
Keywords: Entrepreneurship -- Balkan Peninsula; Economic development -- Balkan Peninsula; New business enterprises -- Balkan Peninsula; Business & Economics -- Entrepreneurship; Entrepreneurship